Moral Distress and the Factors Affecting It: A Review Study - Seyede Fatemeh Hoseini Damiri; Fereshteh Araghian Mojarad; Hedayat Jafari (Shahrekord University of Medical Sciences, 2022)
Background and aims: Moral distress is a significant ethical problem in nursing. The aim of this study was to review the studies into nurses' moral distress and its contributing factors. Methods: This was a narrative review. Data were collected through searching several online Persian and English databases, namely Magiran, SID, IranMedex, PubMed, Scopus, and Google Scholar. Search keywords were "moral distress", "moral stress", "ethics", and "nurse". Eligibility criteria were publication in English or Persian, publication between 2010 and 2020, relevance to moral distress, and accessible full-text. Review studies were not included. Results: A total of 44 eligible articles were included. Nurses' moral distress was at moderate level and its contributing factors were personal, psychological, and organizational factors as well as factors related to care quality. Conclusion: Nurses' moral distress is moderate. Personal, psychological, and organizational factors as well as factors related to care quality contribute to moral distress among nurses. Effective management of these factors can prevent damage to nurses and patients and improve the quality of nursing care.